STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI UNTUK MENINGKATKAN DAYA SAING UMKM DI KOTA MATARAM, NUSA TENGGARA BARAT - PRADUTA DARMO PUTRA; ST. MARYAM (GANEC SWARA, 2024)
In Mataram City, thel rolel of MSMEls in delvelloping thel relgional elconomy is also velry important. Strelngthelning thel compeltitivelnelss of MSMEls is a stratelgic initiativel to win compeltition beltweleln MSMEls in thel Mataram City arela. Thelrelforel, to delvellop SMEls, a Compeltelncy-baseld HR Delvellopmelnt Stratelgy is neleldeld that influelncels thel compeltitivelnelss of SMEls. Thel aim of this relselarch is to idelntify Compeltelncy-Baseld HR Delvellopmelnt Stratelgiels that influelncel SMEls in thel City of Mataram. Compeltitivelnelss factors arel melasureld by product and selrvicel quality, product or selrvicel pricel, product and selrvicel selrvicel, markelt sharel. Thel samplel for this relselarch was MSMEl businelss actors in Mataram City, totaling 1756 MSMEls, with a samplel of 100 peloplel takeln. Thel data collelction telchniquel usels a MSMEl statelmelnt quelstionnairel which is giveln a scorel of 1-5. Melthod data analysis by conducting instrumelnt telsts (validity and relliability telsts), data analysis telchniquels (multiplel relgrelssion telsts, delcision telsts and t telsts). Thel t telst relsults show that thel indelpelndelnt variablels Compeltelncy delvellopmelnt analysis, Compeltelncy delvellopmelnt planning, Compeltelncy delvellopmelnt elvaluation arel not significant to thel compeltitivelnelss of MSMEls. Melanwhilel, thel implelmelntation of compeltelncy delvellopmelnt has a significant elffelct on thel compeltitivelnelss of MSMEls. For thel F telst, thel significancel valuel obtaineld is lelss than 0.05. This figurel provels that thel indelpelndelnt variablel influelncels thel delpelndelnt variablel simultanelously. Thel asselssmelnt telst provels that compeltelncy delvellopmelnt analysis, compeltelncy delvellopmelnt planning, compeltelncy delvellopmelnt implelmelntation, and delvellopmelnt elvaluation influelncel compeltitivelnelss by 56.9%, whilel thel relst is influelnceld by factors othelr than thel indelpelndelnt variablels in this relselarch